Permafrost und seine Auswirkungen auf die Ökologie von Hochgebirgsseen - Thaler, B.; Tait, D.; Tolotti, M. (country:IT, 2015)
The present study, carried out in the framework of the Interreg IV Italy-Austria project “permaqua”, investigates the effects of the melting of permafrost and particularly of rock glaciers on the ecology of high altitude lakes. The ecological structure of 15 lakes, influenced by rock glaciers to different extents, was compared with the one of 18 unaffected lakes used as reference. The chemical-physical and biological analyses were performed on samples taken in each lake during a single late summer or autumnal sampling. All lakes influenced by melting rock glaciers showed surprisingly high concentrations of sulfate, magnesium, calcium and, in the lakes with acidic pH, increased concentrations of heavy metals were also found. The composition of phytoplankton and phytobenthos was mainly determined by pH and nutrient conditions rather than by the abovementioned changes in chemical omposition induced by melting permafrost and zooplankton densities were unfortunately too low to allow any meaningful comparison. However, differences in the composition of the littoral auna were found between lakes with and without rock glacier influence. The littoral macrozoobenthos of the lakes not influenced by rock glaciers was generally composed of a higher number of species, additionally showing a more regular distribution. The higher diversity score was found to be due to the presence of EPT taxa and other sensitive species. Together with the lower species diversity, rock glacier influenced lakes also showed a different composition of the chironomid communities with dominance of insensitive species. The structure of the meiozoobenthos between lakes with and without rock glaciers present in their watersheds was also found to be different and again characterized by the dominance of species with broad ecological valence. The indirect influence of high sulfate concentrations and other substances delivered to the lake by the rock glacier outflows probably produce environmental conditions which provide a competitive advantage to less ...